Hubungan Pola Makan, Pola Istirahat Dan Pola Kebersihan Pada Anak Pra Sekolah Terhadap Perilaku Hidup Bersih Dan Sehat Di TK Santo Asih Desa Parbagasan Kec. Uluan Tahun 2022 - Anita Martiasari; Retno Sugesti; Shinta Mona Lisca (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Clean and Healthy Living Behavior (PHBS) is a collection of behaviors that are practiced based on individual awareness to prevent health problems. Considering that the number of children in Indonesia is an average of 30% of the total population of Indonesia and school age is the golden age for instilling the values of clean and healthy living behavior (PHBS). The aim is to determine the relationship between eating patterns, rest patterns and hygiene patterns in school children on healthy living behavior in kindergarten. Santo Asih, Parbagasan Village, District. Uluan Year 2022. Method: This type of research is analytical descriptive research using quantitative methods, namely a cross sectional approach. The population in the study were 50 pre-school children at Santo Asih Kindergarten with a sample of 50 people. Results: There is a relationship between eating patterns and PHBS in preschool children at Santoh Asih Kindergarten, Parbagasan Village. The P value obtained is 0.006 because the Pv value ≤ α (0.05) and the OR = 275.00 (23,310-3244,305). There is a relationship between rest patterns and PHBS in preschool children at Santoh Asih Kindergarten, Parbagasan Village. By obtaining a P value of 0.000 because the Pv value ≤ α (0.05) and the OR = 19,000 (4,290-84,143), there is a relationship between cleanliness patterns and PHBS in preschool children at Santoh Asih Kindergarten, Parbagasan Village. By obtaining a P value of 0.000 because the Pv value ≤ α (0.05) and the OR = 15,750 (3,625-68,410). In conclusion, there is a relationship between eating patterns, rest patterns, hygiene patterns and clean and healthy living behavior.